2012
DOI: 10.1262/jrd.2012-023
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Luteal Progesterone Concentration and mRNA Expressions of Progesterone Synthesis-related Proteins in the Corpus Luteum of Mares

Abstract: Abstract. Although circulating progesterone (P 4 ) levels tend to change with the season, little is known about the seasonal changes of P 4 synthesis-related proteins in the corpus luteum (CL) of mares. To examine these changes, seventy-four ovaries containing a CL were collected from Anglo-Norman mares at a local abattoir in Kumamoto, Japan (~N32°), five times during one year. The stages of the CLs were classified as early, mid and regressed by macroscopic observation of the CL and follicles. The mid CL, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Pregnenolone leaves the mitochondria and goes to the smooth endoplasmic reticulum, where the enzyme 3β-dehydrogenase hydroxysteroid transforms it into progesterone (Slough et al, 2011). It has been suggested that LH simultaneously increases the expression of the coding genes for StAR protein and the cleavage enzymes of the side chain P450 and 3β-hydroxysteroid dehydrogenase (Beg et al, 2005;Slough et al, 2011;Kozai et al ., 2012).…”
Section: The Production Of Progesteronementioning
confidence: 99%
“…Pregnenolone leaves the mitochondria and goes to the smooth endoplasmic reticulum, where the enzyme 3β-dehydrogenase hydroxysteroid transforms it into progesterone (Slough et al, 2011). It has been suggested that LH simultaneously increases the expression of the coding genes for StAR protein and the cleavage enzymes of the side chain P450 and 3β-hydroxysteroid dehydrogenase (Beg et al, 2005;Slough et al, 2011;Kozai et al ., 2012).…”
Section: The Production Of Progesteronementioning
confidence: 99%